PA.17 Joint perspective, joint decision making; improving maternity bereavement care for stillbirth. A mixed methods multicentre study in the UK providing an in-depth understanding of maternity bereavement care. (9th June 2014) - Chebsey, C; Jackson, S; Gleeson, K; Winter, C; Storey, C; Hillman, J; Lewis, J; Cox, R; Heazell, A; Fox, R; Draycott, T; Siassakos, D
Abstract : Introduction: Research into bereavement care for families who experience perinatal death has been identified as a priority by healthcare organisations, as poor bereavement care is associated with poor long-term outcomes. Method: Semi-structured interviews with bereaved parents after stillbirth, and multidisciplinary focus groups with maternity staff caring for parents. Results: Recruitment rate of 75% exceeded expectations, 24 out of 32 parents agreed to participate. Early analysis suggests certain themes seem relevant to both parents and staff. While the majority of parents were positive about bereavement care, many identified weaknesses and proposed solutions including better training. Poor examples of care that distressed some parents were incomplete awareness of parents' needs, lack of time, and inadequate shared decision-making. "The impression from the doctor was, ' I've got things to do. I'm off'". When being given the news that their baby had died, parents valued an individual and empathetic approach from healthcare professionals that avoided pity or "cold calculated" communication; "Important that [healthcare professionals] can be normal, and talk, and look me in the eye". Parents and staff differed in their approach after the diagnosis; staff appeared to automatically shift care priorities to the mother and their potential future pregnancies, whilst parents continued to focus their concerns on their baby. Conclusion: Communication and decision making is challenging for staff and parents at such a difficult time. A variety of changes may be needed to improve bereavement care, so that parents and staff can understand each other and work together in a very demanding situation.